Why can information not be defined as being purely epistemic? - Krzanowski, Roman (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2020)
The concept of information can be viewed from two perspectives, namely epistemic and ontological. In the epistemic view, information is associated with meaning, semantics, and knowledge, while in the ontological view, it is understood as structures and forms of objects. Information is most often perceived as epistemic information, yet a closer look at epistemic information reveals that this concept does not account for ontological information. This paper poses the following question: Should we select epistemic or ontological information as our primary concept of information, or should we acknowledge that both kinds of information are required for a full comprehension? The discussion here is supported by references to modern research in physics, computing, cosmology, and information sciences.
Keywords: information; epistemic information; ontological information; quantified models of information